1999
DOI: 10.1089/10430349950018409
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Primary Coxsackie and Adenovirus Receptor Is Downregulated during Skeletal Muscle Maturation and Limits the Efficacy of Adenovirus-Mediated Gene Delivery to Muscle Cells

Abstract: Skeletal muscle fibers are infected efficiently by adenoviral vectors only in neonatal animals. This lack of tropism for mature skeletal muscle may be partly due to inefficient binding of adenoviral particles to the cell surface. We evaluated in developing mouse muscle the expression levels of two high-affinity receptors for adenovirus, MHC class I and the coxsackie and adenovirus receptor (CAR). The moderate levels of MHC class I transcripts that were detected in quadriceps, gastrocnemius, and heart muscle di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
153
3
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(168 citation statements)
references
References 27 publications
8
153
3
4
Order By: Relevance
“…The expression level of CAR in human and murine tissues can vary tremendously 3,23 and was found to be highly regulated during murine development. 24,25 In the developing mouse brain, CAR expression peaked in the brains of newborn mice and transfection of murine CAR cDNA increased cell-cell adhesion of murine glioma cells. 25 Previous immunofluorescence studies on lung epithelial tissue cells revealed restriction of CAR to basolateral membranes, with immunostaining most prominently at cell-cell adhesive structures 6 and tight junctions.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of CAR in human and murine tissues can vary tremendously 3,23 and was found to be highly regulated during murine development. 24,25 In the developing mouse brain, CAR expression peaked in the brains of newborn mice and transfection of murine CAR cDNA increased cell-cell adhesion of murine glioma cells. 25 Previous immunofluorescence studies on lung epithelial tissue cells revealed restriction of CAR to basolateral membranes, with immunostaining most prominently at cell-cell adhesive structures 6 and tight junctions.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is caused by a maturation-dependent loss of the myofiber's susceptibility to rAd uptake which is due to structural and biochemical changes during muscle maturation. 5,[12][13][14] When an adenovirus particle enters a target cell, two types of receptor-mediated process are involved. First, the fiber knob of the adenovirus capsid binds to the attachment receptor on the cell surface, such as a Coxsackie B and adenovirus receptor (CAR) [15][16][17][18] and a MHC class I ␣2 domain.…”
Section: Introductionmentioning
confidence: 99%
“…Gene Therapy (2001) 8, 20-27. suggests a high-affinity attachment receptor. 14 This is followed by binding of the penton base to low-affinity internalization receptors, such as ␣ v ␤ 3 , ␣ v ␤ 5 and ␣ 5 ␤ 1 integrins, [20][21][22] which results in internalization of virus capsids. 23 Thus, the densities of attachment and internalization receptors on target cells influence their susceptibility to adenoviral infection.…”
Section: Introductionmentioning
confidence: 99%
“…For Ad vectors, the major viral attachment receptors, coxsackie adenovirus receptor and the integrins a v b3 and a v b5, are downregulated during myoblast differentiation and myofiber maturation. 37,38 Thus, Ad vectors were found to primarily target satellite cells, myoblasts and immature myofibers, and the highest transduction of skeletal muscle mediated by Ad is achieved in neonatal or regenerating muscle tissue. 5,[37][38][39] Effective transduction by VSV-G-pseudotyped lentiviral vectors also requires appropriate expression of several proteins such as heparan sulfate proteoglycans and glycosaminoglycans (GAGs) on target cell surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Thus, Ad vectors were found to primarily target satellite cells, myoblasts and immature myofibers, and the highest transduction of skeletal muscle mediated by Ad is achieved in neonatal or regenerating muscle tissue. 5,[37][38][39] Effective transduction by VSV-G-pseudotyped lentiviral vectors also requires appropriate expression of several proteins such as heparan sulfate proteoglycans and glycosaminoglycans (GAGs) on target cell surfaces. 40 However, the seeming inefficiency of lentiviral transduction of muscle in vivo relative to cultured cell lines may not be due primarily to differences in receptor levels, since we efficiently transduced freshly isolated single myofiber fragments and primary myoblasts from mice (Figures 4a, b, and 5b).…”
Section: Discussionmentioning
confidence: 99%